In-vitro study of Limosilactobacillus fermentum PCC adhesion to and integrity of the Caco-2 cell monolayers as affected by pectins - Srimahaeak, Thanyaporn; Bianchi, Fernanda [UNESP]; Chlumsky, Ondrej; Larsen, Nadja; Jespersen, Lene (Elsevier, 2021)
This study investigated the effect of four citrus pectins on adhesion of the probiotic Limosilactobacillus fermentum PCC and integrity of the intestinal epithelial monolayers using the Caco-2 cell model. Adhesion of L. fermentum PCC was enhanced (from 35% to 54–73%) in the presence of pectins with high and moderate degree of esterification (DE), whereas it was reduced (to 2%) by a pectin with low DE. Transepithelial electrical resistance (TEER) was significantly increased upon exposure to L. fermentum PCC alone (by 33%) and, to a greater extent, by combinations with pectins (by 44 – 48%), suggesting synergistic action of bacteria and pectins. Increases in TEER were related to transcriptional responses of the tight junction genes, encoding claudin-4 and claudin-2 proteins. The overall results indicated that pectins, when applied in synbiotic combination with L. fermentum PCC, have potential to improve bacterial adhesion and the intestinal epithelial barrier.
Keywords: Adhesion; Caco-2 cells; LimosiLactobacillus fermentum PCC; Pectins; Tight junction